THE INFLUENCE OF THE SERVICE PROCESS ON EMPLOYEE PERFORMANCE AT PT PEGADAIAN REGIONAL OFFICE 1 MEDAN - Nasution, Mutiara; Rostinam, Cut Fitri (Jurnal Kelola: Jurnal Ilmu Sosial, 2023)
The aim of this investigation was to ascertain and assess the impact of the Service Process on the performance of employees at PT Pegadaian Regional Office 1 Medan. The research employed quantitative research methods, and the study's population comprised 40 individuals, utilizing saturated sampling as the sampling technique. Through the analysis of research findings, it was deduced that the Service Process exerted a 38.7% influence on performance, with the remaining 61.3% being attributed to unexplored factors. The service process variable exhibited a partially positive and significant impact on performance, evident in the tcount value of 4.893 surpassing the ttable value (1.685). The alternative hypothesis was accepted, while the null hypothesis was rejected.